Correction: Shelat, K.J.; et al. Overall Nutritional and Sensory Profile of Different Species of Australian Wattle Seeds (Acacia spp.): Potential Food Sources in the Arid and Semi-Arid Regions. Foods 2019, 8, 482 - Kinnari J. Shelat; Oladipupo Q. Adiamo; Sandra M. Olarte Mantilla; Heather E. Smyth; Ujang Tinggi; Sarah Hickey; Broder Rühmann; Volker Sieber; Yasmina Sultanbawa (Foods, 2021)
The authors wish to make the following correction to the paper [1]:The title of Table 3 “Amino acid (g/100 g dry weight) profile of four different species of wattle seeds” should be changed to “Amino acid (mol% dry weight) profile of four different species of wattle seeds” [...]